Stakeholder pressure on carbon emissions: strategies and the use of management accounting. Issue 4 (2nd October 2017) - Kumarasiri, Jayanthi
ABSTRACT: Prior research finds corporate environmental behaviour to be a function of stakeholder pressure, which significantly impacts on organisational strategies and internal management practices relating to environmental issues. Applying Freeman's propositions on stakeholder management and corporate strategies, this study explains the relationship among stakeholder pressure, companies' climate change risk management strategies and management accounting practices. Evidence provided through interviews with 39 managers responsible for carbon emissions management within 18 large listed Australian companies is used to investigate these relationships. This study finds that the sample companies used different strategies in accordance with relative cooperative potential and the relative competitive threat posed by stakeholders in managing carbon emissions issues. It is also seen that companies use management accounting techniques as a risk management tool in supporting their climate change strategies.